Peran Layanan Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatkan Konsep Diri Siswa SMAN 1 SEI Kepayang - Deni Rizky Wahyudi; , Ali Daud Hasibuan (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The topic of this essay is The Role of Group Guidance Services Using Play Techniques to Raise Student Awareness in the Next Academic Year. The aims of this study were to: 1) Understand the benefits of role playing in classroom settings for guidance students at SMAN 1 Sei Kepayang. 2) understand the implementation of group guidance services in order to increase student confidence in SMAN 1 Sei Kepayang. 3) Understand the results and short term plans for group guidance services in order to increase the level of student confidence in SMAN 1 Sei Kepayang. The method I use in this research is a qualitative descriptive methodology using qualitative descriptive research. The author uses data collection techniques through observation, interviews, and document analysis in order to obtain the required information. Data collection, data reduction, data presentation, drawing conclusions, or data verification are examples of data processing techniques. The results of the research are: a) group guidance service planning is carried out by identifying students' self-concept problems, assigning group members, determining the time of service implementation, and completing the administration of group guidance service implementation, b) group guidance service implementation is carried out group guidance related to material about student self-concept , in improving students' self-concept. c) Interviews with students as a result of the implementation of group guidance services in terms of increasing students' perceptions of themselves and providing more information are the results of the project.